PENGARUH MODAL KOGNITIF DAN MODAL OPTIMISME TERHADAP KOMITMEN BERKELANJUTAN DIMEDIASI OLEH KOMITMEN NORMATIF (Studi pada Guru Sekolah Dasar Negeri Kecamatan Patebon Kabupaten Kendal) - Hartanti, NIken (Jurnal Ilmiah Telaah Manajemen, 2017)
This study aims to determine to determine the effect of cognitive social capital and optimism psychology capital on continuing commitment mediated by normative commitment.Testing the hypothesis in this study using multiple regression test.The results showed that : (1) Cognitive social capital and optimism psychology capital positive and significant effect on normative commitment. (2) Cognitive social capital and optimism psychology capital also positive and significant impact on the continuing commitment. (3) Normative commitment positive and significant effect on the continuing commitment. (4) Normative commitment mediating the effects of cognitive social capital on continuing commitment. Keywords : Cognitive social capital, optimism psychology capital, normative commitment and a continuing commitment